Islam Modern Era Abad 21 - Samsudin Samsudin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2018)
The decline of Islamic civilization resulted in poverty, ignorance and backwardness suffered by the Muslim community of Western nations. Various awareness emerged in response to it. Whether in the form of systematic movement and individual enlightenment. Both are geared towards efforts to advance the Muslim community in responding to changing times that have never previously predicted. It runs with an initial understanding that Islam is not just a static doctrine,but also became an inspiration for the progress of civilization. In this level, interpreted as a doctrine of Islam that is dynamic, so that according to modern times though. At certain levels, Islam is also interpreted as a “tool” to solve the various problems faced by modern man.